Total body irradiation in allogeneic bone marrow transplantation conditioning regimens: A review. (March 2018) - Paix, Adrien; Antoni, Delphine; Waissi, Waisse; Ledoux, Marie-Pierre; Bilger, Karin; Fornecker, Luc; Noel, Georges
Abstract: Hematologic malignancies may require, at one point during their treatment, allogeneic bone marrow transplantation. Total body irradiation combined with chemotherapy or radiomimetic used in allogeneic bone marrow transplantation is known to be very toxic. Total body irradiation (TBI) induces immunosuppression to prevent the rejection of donor marrow. TBI is also used to eradicate malignant cells and is in sanctuary organs that are not reached by chemotherapy drugs. TBI has evolved since its introduction in the late fifties, but acute and late toxicities remain. Helical tomotherapy, which is widely used for some solid tumors, is a path for the improvement of outcomes and toxicities in TBI because of its sparing capacities. In this article, we first review the practical aspects of TBI with patient positioning, radiobiological considerations and total dose and fractionation prescriptions. Second, we review the use of intensity modulated radiation therapy in bone marrow transplantation with a focus on helical tomotherapy TBI, helical tomotherapy total marrow irradiation (TMI) and total marrow and lymphoid irradiation (TMLI) and their dosimetric and clinical outcomes. Finally, we review the perspective of dose escalation and the extension to older patients and patients with comorbidity who do not benefit from a standard bone marrow transplantation conditioning regimen.